1991
DOI: 10.1042/bj2740535
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human platelets with laminin and identification of the 67 kDa laminin receptor on platelets

Abstract: A microtitre adhesion assay has been developed to define parameters affecting the adherence of washed platelets to laminin. Adherence was optimally supported by Mg2+ and was inhibited by Ca2+ and by anti-laminin Fab fragments, but significant adhesion (75-90% of control) was found both in heparinized plasma containing physiological levels of bivalent cations and in plasma anti-coagulated with EGTA. Adherence was unaffected by platelet activation with ADP but was decreased by 50% by treatment with alpha-thrombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 38 publications
2
81
1
Order By: Relevance
“…Sequence comparison revealed that the two independently identified glycoproteins are the same. FAT/ CD36 has been shown also to be involved in foam cell formation in early atherosclerosis (6,7), in apoptosis (8), and in angiogenesis (9) by recognizing a variety of ligands such as longchain fatty acid (10), anionic phospholipids (11), apoptotic cells (7), thrombospondin (12), and collagen (13).…”
Section: Fatmentioning
confidence: 99%
“…Sequence comparison revealed that the two independently identified glycoproteins are the same. FAT/ CD36 has been shown also to be involved in foam cell formation in early atherosclerosis (6,7), in apoptosis (8), and in angiogenesis (9) by recognizing a variety of ligands such as longchain fatty acid (10), anionic phospholipids (11), apoptotic cells (7), thrombospondin (12), and collagen (13).…”
Section: Fatmentioning
confidence: 99%
“…Collagen-induced platelet responses can be induced by multiple collagen receptors, including glycoprotein VI (GPVI)/Fc receptor ␥ (FcR␥) complex, integrin ␣ 2 ␤ 1 , glycoprotein IV, etc. (2,3). GPVI/FcR␥ signals via the immunoreceptor tyrosine-based activation motif (ITAM)-Syk signaling pathway, and GPVI signaling can be stimulated by GPVI-selective agonists, collagen-related peptide (CRP), and convulxin (4 -6).…”
mentioning
confidence: 99%
“…The role of additional collagen receptors (e.g. GPIV and P65) remains to be elucidated (5,6). On the other hand, thrombin activation of PAR1, but not PAR4, is involved with the formation of the signaling pathway necessary for exposure of negatively charged molecules that increase platelet pro-coagulant activity (7,8); in addition, GPIb and GPV seem to be a positive and a negative modulator of thrombin-induced platelet aggregation, respectively, by a mechanism not fully understood (9).…”
mentioning
confidence: 99%